Factors associated with treatment failure of direct‐acting antivirals for chronic hepatitis C: A real‐world nationwide hepatitis C virus registry programme in Taiwan. (12th March 2021) - Chen, Chi‐Yi; Huang, Chung‐Feng; Cheng, Pin‐Nan; Tseng, Kuo‐Chih; Lo, Ching‐Chu; Kuo, Hsing‐Tao; Huang, Yi‐Hsiang; Tai, Chi‐Ming; Peng, Cheng‐Yuan; Bair, Ming‐Jong; Chen, Chien‐Hung; Yeh, Ming‐Lun; et al.
Abstract: Background/aims: Direct‐acting antivirals (DAAs) are highly effective in treating chronic hepatitis C virus (HCV)‐infected patients. The real‐world treatment outcome in Taiwanese patients on a nationwide basis is elusive. Methods: The Taiwan HCV Registry ( TACR) programme is a nationwide registry platform including 48 study sites, which is organized and supervised by the Taiwan Association for the Study of the Liver. The primary endpoint was sustained virological response (SVR12, undetectable HCV RNA 12 weeks after end‐of‐treatment). Results: A total of 13 951 registered patients with SVR12 data available were analysed (mean age, 63.0 years; female, 55.9%; HCV genotype‐1 [GT1], 57.9%; cirrhosis, 38.4%; preexisting hepatocellular carcinoma [HCC], 10.6%; and hepatitis B virus coinfection, 7.7%). The overall SVR12 rate was 98.3%, with 98.7%, 98.0%, 98.4% and 97.4% in treatment‐naïve noncirrhotic, treatment‐naïve cirrhotic, treatment‐experienced noncirrhotic and treatment‐experienced cirrhotic patients, respectively. The SVR12 rate was > 95% across all subgroups except treatment‐experienced cirrhotic patients who received sofosbuvir/ribavirin (88.7%), treatment‐naïve noncirrhotic patients (94.8%) and treatment‐experienced cirrhotic (94.8%) patients who received daclatasvir/asunaprevir. The most important factor associated with treatment failure was DAA adherence < 60% ( adjusted odds ratio [aOR]/95% confidence interval [CI]: 117.1/52.4‐261.3, P < .001), followed by GT3/GT2 (aOR/CI: 5.78/2.25‐14.9, P = .0003 and aOR/CI: 1.55/1.05‐2.29, P = .03, compared with GT1), active hepatocellular carcinoma (aOR/CI: 4.29/2.57‐7.16, P < .001), the use of sofosbuvir/ribavirin (aOR/CI: 2.51/1.67‐3.77, P < .001) and daclatasvir/asunaprevir (aOR/CI: 3.29/1.94‐5.58, P < .001), decompensated liver cirrhosis (aOR/CI: 2.50/1.20‐5.22, P = .02) and high HCV viral loads (aOR/CI: 2.16/1.57‐2.97, P < .001). Conclusions: DAAs are highly effective in treating Taiwanese HCV patients in the real‐world setting. Maintaining DAA adherence and selecting highly efficacious regimens are keys to ensure treatment success.